Climatological risk: droughts - van Lanen, Henny (2017)
Drought is one of the most complex and severe weather-related natural disasters and its causes and multifaceted impacts are often not well understood. Droughts can last from a season to multiple years, and even decades, and cover small watersheds to hundreds of thousands of hectares. In Europe, drought is a recurrent phenomenon, affecting extended areas and large populations annually (Vogt and Somma, 2000). Across the world, millions of people are annually exposed to droughts that seriously affect economic development and environment. While fatalities mainly occur in poor economies, even in more prosperous regions many people die as a result of indirect effects (e.g. Tallaksen and Van Lanen, 2004; WMO and GWP, 2014). In Europe, almost 80 000 excess fatalities as a result of heatwaves (see Chapter 3.8) and forest fires (see Chapter 3.10) associated with droughts were reported over the period 1998-2009 (EEA, 2011). UNESCO notes that drought can have economic consequences that can go far beyond the immediately impacted areas, such as persistent unemployment and threats to food security, regularly leading to forced migration and social instability (WWAP, 2016). The World Economic Forum (2015) labelled the water crisis as first on the list of factors with a risk of severe impacts for the global community. As one of the reasons for this crisis, drought is likely to become more frequent and severe in the 21st century in many regions of the world, especially in already water-scarce and vulnerable areas, including parts of Europe (IPCC, 2012, 2014).